Factors associated with abdominal obesity among HIV-infected adults on antiretroviral therapy in Malaysia - Hejazi, Nazisa; Huang, Mary Soo Lee; Khor, Geok Lin; Lee, Christopher Kwok Choong (Canadian Center of Science and Education, 2010)
Abdominal or central obesity is a common morphological alteration among HIV-infected subjects on antiretroviral treatment. There is concern that this condition places the subjects at risk of cardiovascular disease. This is a cross-sectional study of 334, HIV-infected adult subjects on antiretroviral therapy at a public hospital in Malaysia. It was aimed at determining the association between nutritional factors and abdominal obesity among PLHIV receiving antiretroviral treatment. Abdominal obesity was prevalent in 36.5% of the respondents. Respondents with abdominal obesity were significantly (p<0.05) older in age, had significantly higher blood triglycerides, fasting plasma glucose, lower HDL-cholesterol, higher BMI at the start of medication and also at the time of the study, bigger waist circumference, higher waist hip ratio, body fat mass, systolic and diastolic blood pressure. They also had lower mean CD4 cell count at start of medication and body lean mass than those without abdominal obesity. After adjusting for the covariates, a significant higher risk of abdominal obesity were observed in those who were older (adjusted OR=1.053, CI=1.012-1.095), had higher fasting plasma glucose (adjusted OR=1.189, CI=1.014-1.394), higher BMI at the time of study (adjusted OR=1.426, CI=1.215-1.674). Being Malay was a protective factor (adjusted OR=0.264, CI=00.102-0.685) for abdominal obesity. These results suggest that care of the HIV-infected population must include intervention to address abdominal obesity in order to provide better quality of life.